Outage Probability of Mixed THz-UWOC Transmission Systems With Hardware Impairments - Shenghai Chen; Lili Wan; Xianwu Mi (IEEE Access)
In this paper, we propose a mixed dual-hop communication system consisting of terahertz/underwater wireless optical communication (THz-UWOC) links with hardware impairments. In particular, considering the heterodyne detection, we assume that the THz link obeys $α $ - $μ $ fading with pointing errors (PEs), while the UWOC channel experiences a mixture exponential-generalized gamma (EGG) fading with pointing errors. Assuming a fixed gain amplify-and-forward (AF) and decode-and-forward (DF) relaying protocols, the closed-form expressions of the outage probability, in terms of the bivariate Fox’s H-function is derived. Finally, the Monte Carlo simulation verifies the analytical results, which demonstrates the effect of turbulence conditions, different fading, and pointing errors on the system performance.